A novel ratiometric fluorescent probe based on thienocoumarin and its application for the selective detection of hypochlorite in real water samples and in vivo. (6th April 2020) - Shi, Lei; Yu, Huijuan; Zeng, Xianqing; Yang, Sheng; Gong, Shengzhao; Xiang, Hua; Zhang, Kai; Shao, Guang
Abstract : A novel ratiometric fluorescent probe based on thieno[3, 2- c ]coumarin has been prepared for sensing hypochlorite, which could exhibit a large emission shift and a 338-fold emission ratio ( I 470 / I 640 ). Abstract : As one of the reactive oxygen species (ROS), the concentration of hypochlorite (HClO/ClO − ) in the environment and in vivo is associated with many diseases and is also quite significant for human health. In this paper, a novel ratiometric fluorescent probe CSN based on thieno[3, 2- c ]coumarin has been constructed for the detection of hypochlorite. This probe exhibited high selectivity and sensitivity towards HClO/ClO −, and showed a large emission shift (170 nm) and a 338-fold enhancement in the emission ratio ( I 470 / I 640 ). Moreover, investigations for sensing hypochlorite in real water samples and bioimaging in living cells were carried out, and the test results have confirmed the high potential of probe CSN in analytical and bioanalytical applications.